1999
DOI: 10.1001/archinte.159.22.2681
|View full text |Cite|
|
Sign up to set email alerts
|

Cranial Computed Tomography Before Lumbar Puncture

Abstract: Because of the low prevalence of lesions that contraindicate LP, screening cranial CT solely to establish the safety of performing an LP typically provides limited additional information. Physicians can use their overall clinical impression and 3 clinical predictors to identify patients with the greatest risk of having intracranial lesions that may contraindicate LP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
35
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 91 publications
(39 citation statements)
references
References 34 publications
3
35
1
Order By: Relevance
“…Interposition of CT scanning before lumbar puncture delayed initiation of antibiotic therapy by an average of 2 hours. Similar data on delay of initiation of treatment were reported by Gopal et al 17 and Linden et al 22 In the hospital setting of the study reported by Talan et al, CT scanning was available 24 hours a day. Even in settings where CT examination can be completed in 15 to 20 minutes, there is always the possibility of unexpected delay.…”
Section: Ct Examination Risks a Delay In Start Of Antimicrobial Managsupporting
confidence: 73%
“…Interposition of CT scanning before lumbar puncture delayed initiation of antibiotic therapy by an average of 2 hours. Similar data on delay of initiation of treatment were reported by Gopal et al 17 and Linden et al 22 In the hospital setting of the study reported by Talan et al, CT scanning was available 24 hours a day. Even in settings where CT examination can be completed in 15 to 20 minutes, there is always the possibility of unexpected delay.…”
Section: Ct Examination Risks a Delay In Start Of Antimicrobial Managsupporting
confidence: 73%
“…Altered mentation (likelihood ratio [LR], 2.2; 95% confidence interval [CI], 1.5-3.2), focal neurological finding (LR, 4.3; 95% CI, 1.9-10), and papilledema (LR, 11; 95% CI, 1.1-115) increased the likelihood of an intracranial lesion. 12 Overall clinical impression (not defined in the study) was able to identify patients with a CT-defined contraindication to LP (LR, 19; 95% CI, 4.8-43). In a second prospective study of 301 patients with suspected meningitis, 235 underwent a CT scan prior to LP.…”
Section: What Are the Contraindications To Performing An Lp?mentioning
confidence: 87%
“…In a prospective study, 113 patients were examined by internal medicine residents (overseen by emergency physicians) prior to undergoing computed tomography (CT) of the brain and subsequent LP. 12 The median age of patients was 42 years, 36% were immunocompromised, and 46% of patients had altered mentation. Altered mentation (likelihood ratio [LR], 2.2; 95% confidence interval [CI], 1.5-3.2), focal neurological finding (LR, 4.3; 95% CI, 1.9-10), and papilledema (LR, 11; 95% CI, 1.1-115) increased the likelihood of an intracranial lesion.…”
Section: What Are the Contraindications To Performing An Lp?mentioning
confidence: 99%
See 1 more Smart Citation
“…In such cases, the damaged tissue will not be repaired [3]. When it comes to negative effects on human body, natural radiation is considered as a very important phenomenon.…”
Section: Introductionmentioning
confidence: 99%